The Role of Teacher-Parent Communication in Enhancing Students' Learning Motivation at Mts Maarif, Limboro, Polewali Mandar - Herlina (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to 1) identify the forms of communication between teachers and parents that enhance student motivation at Mts Maarif Limboro, 2) determine the role of teacher communication in boosting student learning motivation at Mts Maarif Limboro, 3) examine the role of parent communication in enhancing student learning motivation at Mts Maarif Limboro, 4) identify the barriers teachers face in improving student learning motivation at Mts Maarif Limboro, and 5) explore the challenges parents face in enhancing their children's learning motivation at Mts Maarif Limboro. This research adopts a field study approach with a qualitative methodology. The primary data sources include eighth-grade homeroom teachers, Fikih teachers, parents of students, and eighth-grade students. Data collection was conducted through interviews with relevant parties, including eighth-grade homeroom teachers, Fikih teachers, parents, and eighth-grade students, as well as through observation and documentation. The credibility of the data was ensured using triangulation techniques. The data analysis process involved data reduction, data presentation, and conclusion drawing. The findings indicate that 1) the form of communication used by teachers and parents is interpersonal communication, 2) the role of teacher communication with students involves educating and motivating, 3) the role of parent communication with children involves guiding and facilitating their learning needs, 4) the barriers teachers face in increasing student motivation include students' lack of receptiveness to the material and ineffective interpersonal relationships among students, and 5) the barriers parents face in enhancing their children's learning motivation include limited interaction time at home and economic conditions.